1999
DOI: 10.1042/bj3450069
|View full text |Cite
|
Sign up to set email alerts
|

Influence of spermine on intestinal maturation of the glycoprotein glycosylation process in neonatal rats

Abstract: Previous work has shown an inverse evolution of the rat intestinal glycoprotein sialylation that decreases from birth to weaning and of fucosylation that increases markedly after weaning during postnatal development. At weaning time, an increase in the intestinal level of polyamines (and especially that of spermine) was observed, owing partly to the higher level of spermine found in solid food given to rats at this period in comparison with the level found in milk. To study the role of this polyamine as a poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…The most profound changes are observed in the epithelium of the small intestine. Developmental adaption of small intestinal enterocytes is considered to be preprogrammed, but several studies have suggested that external stimuli, such as microbial colonization and diet, may modulate the timing of age-related changes during early postnatal life (1)(2)(3)(4)(5). The joint action of environmental and intrinsic stimuli may therefore be responsible for initiating the adaptive changes and influence the precise timing and the level of expression of specific intestinal markers.…”
mentioning
confidence: 99%
“…The most profound changes are observed in the epithelium of the small intestine. Developmental adaption of small intestinal enterocytes is considered to be preprogrammed, but several studies have suggested that external stimuli, such as microbial colonization and diet, may modulate the timing of age-related changes during early postnatal life (1)(2)(3)(4)(5). The joint action of environmental and intrinsic stimuli may therefore be responsible for initiating the adaptive changes and influence the precise timing and the level of expression of specific intestinal markers.…”
mentioning
confidence: 99%
“…The dose and concentration of SPM selected for the present experiments approximated those used by previous investigators to induce the maturation of the intestine in animals. [10][11][12][13][14][15] The dose of SPM used in the present study is well within normal limits.…”
Section: Discussionmentioning
confidence: 70%
“…8,9) Oral administration of SPM induces precocious maturation of the intestine. [10][11][12][13][14][15] Oral polyamines have also been shown to have beneficial effects on healing 16,17) and prevention [18][19][20] of gastrointestinal damage.The gastrointestinal tract acts as a barrier against the invasion of exogenous proteins into the body. This barrier function is due to enzymes that degrade the proteins and also due to impermeability of the proteins to the membrane due to their large molecular weight.…”
mentioning
confidence: 99%
“…The polyamine determinations were performed as previously described (33). Briefly, the small intestines (from the gastroduodenal junction to the ileocecal junction) were quickly removed and washed with 9 g/L saline solution at 4°C.…”
Section: Methodsmentioning
confidence: 99%
“…An internal standard was added, and the proteins were discarded after precipitation. After derivatization with 1 mM 9-fluorenylmethyl chloroformate for 45 s at room temperature, the polyamines were separated by HPLC, as previously described (33), identified by their retention times, and quantified by comparison with standard concentration curves, using 1,6-hexanediamine as an internal standard.…”
Section: Methodsmentioning
confidence: 99%